2014
DOI: 10.14740/jocmr1843w
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of Red Blood Cells Is Associated With Improved Central Venous Oxygen Saturation But Not Mortality in Septic Shock Patients

Abstract: BackgroundAlthough the optimum hemoglobin (H) concentration for patients with septic shock (SS) has not been specifically investigated, current guidelines suggest that H of 7 - 9 g/dL, compared with 10 - 12 g/dL, was not associated with increased mortality in critically ill adults. This contrasts with early goal-directed resuscitation protocols that use a target hematocrit of 30% in patients with low central venous oxygen saturation (ScvO2) during the first 6 hours of resuscitation of SS.MethodsData elements w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Much of the uncertainty in RBC transfusion stems from the fact that it is not currently possible to quantify anemia risk and balance that against risk of donor RBCs. There are many technologies attempting to infer risk of anemia, but to date we lack biomarkers that fulfill Prentice criteria (9, 6567). As such, there is a plurality of perspectives and clinical practice regarding RBC transfusion (64), (54).…”
Section: Current Strategies and Future Directions In Transfusion Decimentioning
confidence: 99%
“…Much of the uncertainty in RBC transfusion stems from the fact that it is not currently possible to quantify anemia risk and balance that against risk of donor RBCs. There are many technologies attempting to infer risk of anemia, but to date we lack biomarkers that fulfill Prentice criteria (9, 6567). As such, there is a plurality of perspectives and clinical practice regarding RBC transfusion (64), (54).…”
Section: Current Strategies and Future Directions In Transfusion Decimentioning
confidence: 99%
“…A normalization of anemia in chronic kidney disease did not reduce the risk of cardiovascular events and did not improve quality of life but did increase the risk of stroke and death . In septic shock, critical care, and acute upper gastrointestinal bleeding, a restrictive transfusion regimen was as effective as or even superior to a liberal transfusion regimen. Treatment of anemia in chronic heart failure had no clinical benefit .…”
Section: Discussionmentioning
confidence: 94%
“…Data from the subgroup analysis performed by Gilbert et al, ( 24 ) Silverman et al, ( 25 ) Sadaka et al, ( 26 ) and Mazza et al ( 14 ) were abstracted and analyzed separately because we considered that each subgroup represented a different population.…”
Section: Resultsmentioning
confidence: 99%
“…The Level of Evidence analyzed through the ELIS system revealed that 5 studies met the criteria for level II evidence, ( 11 , 14 , 26 - 28 ) 8 studies were classified as level III, ( 12 , 24 , 25 , 29 - 33 ) and the remaining were level IV ( ).…”
Section: Resultsmentioning
confidence: 99%